2021
DOI: 10.1101/2021.01.24.428007
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of mutations in the SARS-CoV-2 spike protein on protein stability, cleavage, and cell-cell fusion function

Abstract: The SARS-CoV-2 spike protein (S) is the sole viral protein responsible for both viral binding to a host cell and the membrane fusion event needed for cell entry. In addition to facilitating fusion needed for viral entry, S can also drive cell-cell fusion, a pathogenic effect observed in the lungs of SARS-CoV-2 infected patients. While several studies have investigated S requirements involved in viral particle entry, examination of S stability and factors involved in S cell-cell fusion remain limited. We demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 108 publications
0
4
0
Order By: Relevance
“…The S2 is markedly conserved among CoVs, and have a low mutation rate indicating that most mutations are likely to impact viral entry. Moreover, it is less antigenic, probably due to the extensive N-linked glycosylation, therefore not under much selective pressure compared to S1 ( 9 , 27 ). However, studies show the HR2 region can elicit an antibody response that is cross-reactive with other CoVs ( 28 ).…”
Section: Variations In Sars-cov-2 Genome and Proteomementioning
confidence: 99%
“…The S2 is markedly conserved among CoVs, and have a low mutation rate indicating that most mutations are likely to impact viral entry. Moreover, it is less antigenic, probably due to the extensive N-linked glycosylation, therefore not under much selective pressure compared to S1 ( 9 , 27 ). However, studies show the HR2 region can elicit an antibody response that is cross-reactive with other CoVs ( 28 ).…”
Section: Variations In Sars-cov-2 Genome and Proteomementioning
confidence: 99%
“…Notably, during the evolution of SARS-CoV-2, the S1-NTD in the present study additionally organized many mutations, including deletions idel69/70 and del 142/144. Similarly, frequently deleted regions in the NTD were those positioned at 69-70, 141-144, 146, 210, and 243-244; reported in the previous study most NTD mutations were found to change antigenicity or eliminate epitopes, enabling immune escape (52).…”
Section: Resultsmentioning
confidence: 54%
“…reported in the previous study, most NTD mutations were found to change antigenicity or eliminate epitopes, enabling immune escape. (32).…”
Section: Resultsmentioning
confidence: 99%